SPIRITUAL PRECURSORS OF POSTMODERNISM (Heritage, 2022)
Contemporary postmodernism in philosophy for its rising is due to its spiritual precursors of the 18th and 19th century. It is featured by the criticism of the enlightenment philosophy based on leading role of reason in knowledge. Precursors of postmodernism personified in Kant, Kierkegaard, Nietzsche and Heidegger severely criticized a prevailing role of reason in knowledge process and reaching of truth. There is no absolute truth and individualism.                The relationship between knowledge and power is also subject to change: it is changed their positions related to famous Bacon’s „knowledge is power“ in order to reach new “postmodern condition”, which is featured by the absence of metanarratives, giving the importance of small récites and new relationships between readers, writer and text. Such comprehensions were spurred by existentialist philosophy fighting for the survival of man giving primacy of existence over essence.        In what measure postmodernism will be able to respond to many challenges of modern world depends of its adaptability toward modern streams in social sciences and more objective approach to modernism.
Keywords: Kant, Rousseau, Kierkegaard, Nietzsche, Heidegger, precursors, postmodernism, reason, criticism